The organ music of J.S. Bach - Williams, Peter 1937-2016 (Cambridge University Press, 2009)
This is a completely revised 2003 edition of volumes I and II of The Organ Music of J. S. Bach (1980), a bestselling title, which has subsequently become a classic text. This edition takes account of Bach scholarship of the 25 years prior to publication. Peter Williams's piece-by-piece commentary puts the musical sources of the organ works in context, describing the form and content of each work and relating them to other music, German and non-German. He summarises the questions about the history, authenticity, chronology, function and performance of each piece, and points out important details of style and musical quality. The study follows the order of the Bach catalogue (BWV), beginning with the sonatas, then the 'free works', followed by chorales and ending with the doubtful works, including the 'newly discovered chorales' of 1985